2017
DOI: 10.1021/acs.jafc.7b00854
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonation Disposition of Acacetin: In Vitro and in Vivo

Abstract: Acacetin, an important component of acacia honey, exerts extensive therapeutic effects on many cancers. However, the sulfonation disposition of acacetin has rarely been reported. Therefore, this study aimed to investigate the sulfonation disposition of acacetin systematically. The results showed that acacetin-7-sulfate was the main metabolite mediated primarily by sulfotransferases (SULT) 1A1. Dog liver S9 presented the highest formation rate of acacetin-7-sulfate. Compared with that in wild-type Friend Virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…We concluded that BCRP had a significant impact on the elimination of Aca‐7‐S in vivo . This conclusion was supported by a previous report showing that Aca‐7‐S was transported primarily by BCRP and MRP1 in vivo (Zhang et al, ). In addition, BCRP was probably involved in the elimination of Aca‐7‐G but was not the major determinant.…”
Section: Resultssupporting
confidence: 84%
“…We concluded that BCRP had a significant impact on the elimination of Aca‐7‐S in vivo . This conclusion was supported by a previous report showing that Aca‐7‐S was transported primarily by BCRP and MRP1 in vivo (Zhang et al, ). In addition, BCRP was probably involved in the elimination of Aca‐7‐G but was not the major determinant.…”
Section: Resultssupporting
confidence: 84%
“…The molecular formulas were assigned as C 16 H 12 O 8 S, 80 Da (SO 3 ) larger than that of the parent drug. The MS 2 spectra of M14 and M15 presented staple ions at m / z 283.0607 and 268.0369 by continuously dropping SO 3 and CH 3; since their Clog P values were 1.02632 and 1.92632, which were calculated by ChemDraw 14.0, M14 and M15 were respectively identified as acacetin-5- O -sulfate and acacetin-8- O -sulfate …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the liver microsome system has been regarded as a valuable model to study food and drug metabolism in vitro due to the biotransformation organ of the liver . Previously, the monoglucuronide and monosulfate metabolites of acacetin were identified, and their dispositions were investigated. , Nevertheless, to date, no systematic and detailed metabolite data are available, particularly those of acacetin. Therefore, it is indispensable to clarify the metabolites of acacetin.…”
Section: Introductionmentioning
confidence: 99%
“…The reversibility of MAO-B inhibition with acacetin 7-methyl ether adds significant value to its potential therapeutic use. A recent pharmacokinetics study of acacetin metabolism in vitro and in vivo that analysed its metabolites showed that acacetin is metabolized by the sulfotransferase 1A1 enzyme into acacetin-7-sulfate, which was detected in vivo in plasma samples and also in vitro from incubation of the Liver S9 fraction [29].…”
Section: Discussionmentioning
confidence: 99%